Research progress of gut microbiome and diabetic nephropathy - Chu, Chenling; Behera, Tapas Ranjan; Huang, Ying; Qiu, Wenhui; Chen, Jiayi; Shen, Quanquan (Frontiers in Medicine, 2024)
Diabetic nephropathy is an important complication of diabetic microvascular injury, and it is also an important cause of end-stage renal disease. Its high prevalence and disability rate significantly impacts patients' quality of life while imposing substantial social and economic burdens. Gut microbiota affects host metabolism, multiple organ functions, and regulates host health throughout the life cycle. With the rapid development of technology, researchers have found that gut microbiota is closely related to the progression of diabetic kidney disease. This review explores the role of gut microbiome in diabetic nephropathy summarizing proposed mechanisms of progression and focusing on microbial metabolites, intestinal barrier disruption, inflammation, filtration barrier damage and renal fibrosis. This review also examines the mechanism and limitations of current treatments, including drugs, fecal microbiota transplantation, and lifestyle changes, offering new perspectives on prevention and treatment. 1 Introduction According to the data released by the International Diabetes Federation (IDF), there were 537 million diabetes patients in the world in 2021. As the global prevalence of diabetes mellitus (DM) continues to grow, it is projected to rise to 783 million people by 2045 (Magliano et al., 2021).Type 2 diabetes mellitus (T2DM) accounts for more than 90% of the global incidence (Sun et al., 2022).During the prolonged course of diabetes leading to chronic Diabetic nephropathy is a major cause of endstage renal disease.